Female Amerindians in early modern Spanish theater - Robalino, Gladys (Bucknell University Press ; The Rowman and Littlefield Publishing Group, Incorporated, 2014)
This book uses a gender perspective to study the female Amerindian characters in Early Modern Spanish Comedias. The chapters in this collection bring different approaches and perspectives that intersect between feminism and cultural studies while they also critically deconstruct the European representation of Amerindian women.